2004
DOI: 10.1111/j.1365-3156.2004.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age, molecular markers, and response to sulphadoxine–pyrimethamine treatment in Kampala, Uganda

Abstract: Sulphadoxine/pyrimethamine (SP) has become the first-line treatment of uncomplicated malaria in a number of African countries. Molecular surveillance of resistance-mediating mutations in Plasmodium falciparum dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps) has been proposed as a means of predicting SP treatment outcomes, but optimal methods of surveillance in different populations have not been well established. To investigate the relationship between molecular markers of SP resistance, host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
65
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 28 publications
9
65
3
Order By: Relevance
“…The presence of the DHFR-164-Leu mutation is troubling because it confers cross-resistance to Lapdap. In Africa, the DHFR-164 mutation has rarely been found: previous reports of this mutation were from travelers and people treated with Lapdap, and it was also found as a rare component of samples (6,8,15). In contrast, we report the DHFR-164 mutation as a major component of samples in African women who report not taking Lapdap.…”
contrasting
confidence: 56%
“…The presence of the DHFR-164-Leu mutation is troubling because it confers cross-resistance to Lapdap. In Africa, the DHFR-164 mutation has rarely been found: previous reports of this mutation were from travelers and people treated with Lapdap, and it was also found as a rare component of samples (6,8,15). In contrast, we report the DHFR-164 mutation as a major component of samples in African women who report not taking Lapdap.…”
contrasting
confidence: 56%
“…Although triple and quadruple mutants were detected in the samples analyzed in this study, it must be emphasized that the predictive value of these markers varies geographically and involves a complex interplay between host immunity, parasites, and drug. [29][30][31] Overall, the results of this study showed a significant increase in the prevalence of mutations in the P. falciparum dhfr and dhps genes from 2003 to 2010. The combined benefits of low-cost, single-dose administration, and better tolerability as compared with ACTs currently in use in Ghana might It is unclear whether the use of SP for IPTp alone or the use of SP in the general population for the treatment of uncomplicated malaria has contributed to the drug pressure.…”
Section: Discussionmentioning
confidence: 54%
“…The predictive value of the combination of these SNPs varies geographically, depending on, e.g., baseline prevalence, age, and levels of acquired immunity. [18][19][20][21][22] In Africa, the Pfdhfr triple mutant, 51I-59R-108N, together with the Pfdhps double mutant, 437G-540E forms the quintuple mutant that predicts a high risk of treatment failure after SP treatment. 23,21 Similarly, and specifically regarding IPTi, recent evidence suggests that high prevalence ( 50%) of the highly resistant Pfdhps 540E mutantessentially the quintuple Pfdhfr/Pfdhps mutant, may undermine the required protective efficacy of SP-IPTi of 20%.…”
Section: Introductionmentioning
confidence: 99%